Um estudo em azul : as interações e aprendizagens de um menino autista no ensino regular - Amaral, Elexandra Martins de Souza (2019)
This study had as general aim to observe and to acknowledge the form of the interactions and the process of the teaching-learning of August, a boy with Autistic Spectrum Disorder, in the context of the public mato-grossense school. Specifically, it aimed: 1) To comprehend how August interacts with his Portuguese teachers, his caretakers and his classmates; 2) To investigate how his process of teaching-learning of Portuguese occurs; 3) To observe in which measure the affectivity present in his school relations can influence his social and cognitive development. To do so, the present study is anchored in the theoretical assumptions of Bakhtin and the Circle about the social constitution of language and of the subject (1929 [2014]), the exotopy (1979 [2010]) and the active comprehension (1986 [2017]) and in vigotskian concepts of zone of proximal development (1934 [2017]), mechanism of compensation of people with impairment (1828-29 [1997]), and affectivity (1926 [2004]). Also the following TEA scholars are part of the theoretical framework of this research: Whitman (2015), Donvan and Zuckher (2017) and Grandin and Panek (2018). Developed in the light of theoretical and methodological contribution of the social-historical-cultural approach, this study uses qualitative methodology, done through a case study of ethnographic type. To the recollection of the data, it was resorted to the observation, records in the field diary, recordings, photos and interviews with the subjects involved in the research. The data analysis, which was based in Dialogic Analysis of the Discourse (BRAIT, 2006), allowed not only the comprehension of the insertion of August in the different spaces of the school and the notion of the self as an active and participative student was been established through the joint efforts of his mother, his Portuguese teachers, his caretakers, his classmates, as well as the perception of the path he had taken in the search for learning had many advances. The data still indicate the initiative of August’s classmates to interact with him, the mediation of one of the teachers and the affection of one of the caretakers were essential to his social and cognitive development, specially in relation to the comprehension of the emotions of the others and of the situation he was part of.